2016
DOI: 10.1038/srep26809
|View full text |Cite
|
Sign up to set email alerts
|

Ciguatoxin reduces regenerative capacity of axotomized peripheral neurons and delays functional recovery in pre-exposed mice after peripheral nerve injury

Abstract: Ciguatera fish poisoning (CFP) results from consumption of tropical reef fish containing ciguatoxins (CTXs). Pacific (P)-CTX-1 is among the most potent known CTXs and the predominant source of CFP in the endemic region responsible for the majority of neurological symptoms in patients. Chronic and persistent neurological symptoms occur in some CFP patients, which often result in incomplete functional recovery for years. However, the direct effects of exposure to CTXs remain largely unknown. In present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
(109 reference statements)
0
29
0
Order By: Relevance
“…These toxicokinetic factors could contribute to the preferential sensory toxicity of CTXs. Consistent with this, peripheral nerves were the main tissues in which P-CTX-1 was quantified 2 h after intraperitoneal exposure, ahead of the intestine, kidneys, stomach, liver, heart and muscles [ 209 ].…”
Section: Pathophysiological Basis Of Ciguatera Neurological Disturmentioning
confidence: 67%
“…These toxicokinetic factors could contribute to the preferential sensory toxicity of CTXs. Consistent with this, peripheral nerves were the main tissues in which P-CTX-1 was quantified 2 h after intraperitoneal exposure, ahead of the intestine, kidneys, stomach, liver, heart and muscles [ 209 ].…”
Section: Pathophysiological Basis Of Ciguatera Neurological Disturmentioning
confidence: 67%
“…The quality and speed of nerve regeneration is improved when occurring in a well-vascularized site and in the presence of small amounts of scar tissue. Besides mechanical factors, the time elapsed between injury and complete repair and its functional recuperation prognosis depend on factors such as the age of the patient, the type of nerve, the site of the nerve that was injured, the cause of the injury and effect on neighboring tissues resulting from the injury [1,2,41,42]. Nonetheless, even when endogenous repair mechanisms are effective, regenerated nerves often present thinner myelin sheets and shorter nodal lengths and result in functional deficits [43].…”
Section: Wallerian Degeneration Endogenous Regeneration and Responsmentioning
confidence: 99%
“…P-CTX-1 is able to persist in mouse peripheral nerves from several hours to two months after exposure, which may explain the long duration of neurological disturbances. Evidence has shown that the persistence of P-CTX-1 in peripheral nerves inhibits both axonal regrowth after injury and reduces other capacities of peripheral neurons, resulting in delayed functional recovery [ 84 ].…”
Section: Compounds Produced By Gambierdiscus Amentioning
confidence: 99%
“…Gambierol has been shown to induce augmentation of spontaneous Ca 2+ oscillations in cerebrocortical neurons as a consequence of K v channel inhibition. Interestingly, gambierol in these cells produced a concentration-dependent stimulation of neurite outgrowth that was mimicked by 4-aminopyridine, a universal K + -channel inhibitor [ 123 ], in contrast to the abovementioned inhibitory effect of P-CTX-1 in axotomized peripheral neurons [ 84 ].…”
Section: Compounds Produced By Gambierdiscus Amentioning
confidence: 99%